Factors affecting customer satisfaction in banking industry in Tanzania: A case of national microfinance bank (NMB) Bagamoyo branch - Chawinga, Elizabeth (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirements of award of the degree of Master of Business Administration (MBA) of Mzumbe University.